Dobrava Virus Carried by the Yellow-Necked Field Mouse Apodemus flavicollis, Causing Hemorrhagic Fever with Renal Syndrome in Romania - Panculescu-Gatej, Raluca Ioana (Mary Ann Liebert, Inc., 2014)
Hemorrhagic fever with renal syndrome (HFRS) has been confirmed by serological methods during recent years in Romania. In the present study, focus-reduction neutralization tests (FRNT) confirmed Dobrava hantavirus (DOBV) as the causative agent in some HFRS cases, but could not distinguish between DOBV and Saaremaa virus (SAAV) infections in other cases. DOBV was detected by a DOBV-specific TaqMan assay in sera of nine patients out of 22 tested. Partial sequences of the M genomic segment of DOBV were obtained from sera of three patients and revealed the circulation of two DOBV lineages in Romania. Investigation of rodents trapped in Romania found three DOBV-positive Apodemus flavicollis out of 83 rodents tested. Two different DOBV lineages were also detected in A. flavicollis as determined from partial sequences of the M and S genomic segments. Sequences of DOBV in A. flavicollis were either identical or closely related to the sequences obtained from the HFRS patients. The DOBV strains circulating in Romania clustered in two monophyletic groups, together with strains from Slovenia and the north of Greece. This is the first evidence for the circulation of DOBV in wild rodents and for a DOBV etiology of HFRS in Romania.